Analysis of heat treatment effect on fretting fatigue occurrence in Zr-1Nb-1Sn-0.1Fe fuel rods. (October 2021) - Baêta, D.A.; Costa, D.J.R.; Medeiros, N.
Abstract: Nuclear fuel rods prevent the loss of nuclear material to the refrigerant fluid, acting as a first safety barrier. Damage by grid-to-rod fretting remains a significant cause of nuclear fuel element failure in Pressurized Water Reactors (PWR). In this paper fretting-induced friction at the contact interface between springs and samples of nuclear fuel rods of Zr-1.0Nb-1.0Sn-0.1Fe alloy was evaluated. The effect on the fretting resistance of heat treatments applied to the samples of Zr-1.0Nb-1.0Sn-0.1Fe fuel rods was also investigated. It was observed that the increase in the heat treatment temperature decreases the mass loss, indicating a mild fretting wear regime. Graphical abstract: Image 1 Highlights: The nuclear fuel rods prevent the loss of nuclear material to the refrigerant fluid. Damage by grid-to-rod fretting remains a significant cause of nuclear fuel failure. Heat treatment promoted an increase in the Zr–1Nb–1Sn-0.1Fe fretting resistance.